PENGARUH RECEIVABLE TURNOVER TERHADAP RETURN ON EQUITY (ROE) PADA KOPERASI KARYAWAN SEHAT DI PT. SAMWHA INDONESIA - Yuningsih, Any (Directorate of Academic Research and Community Services, 2019)
Employee cooperative is a type of cooperative that still survive until today because they are supported by the payment system from the members to the cooperative using salary deduction which resulted the smoothness of the receivables payment from the members to cooperative, but it still has the possibility of other problems in the financial sector. This study aimed to determine the picture of Receivable Turnover and Return on Equity (ROE) and how was the influence of the Receivable Turnover on Return on Equity (ROE) in Koperasi Karyawan Sehat. This research used a descriptive method with a quantitative approach. The data used were the secondary data from financial report of Koperasi Karyawan Sehat. The sample in this study was the balance sheet in 2010-2015. Non-probability sampling technique presented by purposive sampling was used in this study. Based on the partial hypothesis testing, there was a significant influence between accountsreceivable turnover on Return on Equity (ROE), while the results of the coefficient of determination test indicate that accounts receivable turnover contributes 83, 36% of the variable Return on Equity (ROE). The remaining of 16.64% was contributed by working capital, sales, market share, dividend policy and other factors which was not examined in this study.